(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India is a growing economy. Employee engagement is an absolutely essential of business growth, efficiency and innovation employee retention and customer satisfaction. Employee engagement is the extent to which employees feel passionate about their jobs, are committed to the organization and put discretionary effort into their work. Engaged employees fell a strong emotional bond to the organization that employs them.